2011
DOI: 10.1590/s0036-46652011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio Parahaemolyticus isolated from oysters and mussels in São Paulo, Brazil

Abstract: SUMMARYVibrio parahaemolyticus is a marine bacterium, responsible for gastroenteritis in humans. Most of the clinical isolates produce thermostable direct hemolysin (TDH) and TDH-related hemolysin (TRH) encoded by tdh and trh genes respectively. In this study, twenty-three V. parahaemolyticus, previously isolated from oysters and mussels were analyzed by PCR using specific primers for the 16S rRNA and virulence genes (tdh, trh and tlh) and for resistance to different classes of antibiotics and PFGE. Nineteen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
5
24
4
1
Order By: Relevance
“…All recovered isolates clustered at 40% or higher similarity, which indicates the high intraspecific diversity of this species. Previous investigators (4,46) also found that the PFGE analysis demonstrated high heterogeneity among the V. parahaemolyticus isolated from seafood.…”
Section: Discussionmentioning
confidence: 83%
“…All recovered isolates clustered at 40% or higher similarity, which indicates the high intraspecific diversity of this species. Previous investigators (4,46) also found that the PFGE analysis demonstrated high heterogeneity among the V. parahaemolyticus isolated from seafood.…”
Section: Discussionmentioning
confidence: 83%
“…Both V. parahaemolyticus and V. diabolicus were negative, and V. fluvialis (71%), V. alginolyticus (22%) , V. anguillarum (50%) and V. aestuarianus (100%) were positive for haemolysis. A previous study reported that 15.8% of the V. parahaemolyticus from oysters and mussels were β‐haemolytic (Rojas, Matté, Dropa, Da Silva, & Matté, ). In addition, we could detect five isolates concurrently positive for both slime production and haemolysis, and four of them produced four or more extracellular enzymes which signify their high virulence and pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, 62 people in Alaska were reported to develop foodborne gastroenteritis after eating raw oysters in 2004 (McLaughlin et al, 2005), More recently, an outbreak of F, parahaemolytìcus involving 177 cases was recorded in 2006 and was linked to the consumption of contaminated oysters (CDC 2006). Twenty three Κ parahaemolytìcus strains were isolated using molecular methods from oysters and mussels, collected from aquatic environments, fish markets and restaurants in Säo Paulo, Brazil, between February 1989 and January 1990 (Rojas et al 2011 ). In this study, the tlh gene was present in 100% of isolates, the tdh gene was identified in two (10.5%) isolates, whereas the gene trh was not detected.…”
Section: Vibrio Parahaemolytìcus and Seafood Outbreaksmentioning
confidence: 75%